(untitled) (The Journal of Plant Protection Sciences, 2020)
The present experiment on snap melon [Cucumis melo (L.)var. momordica Duth.&Full.], was carried out during 2004-2005 to determine the best sowing date for higher female flower production and more number of fruits as well as lower fruit fly incidence. Three sowing dates viz. S1=25 November, 2004, S2=25 January 2005 and S3 =25 March, 2005 were selected to evaluate performance of eight genotypes, named as BCSM-1 to BCSM-8. The experimental design was factorial RBD with 3 replications. Observations on days to first male and female flowers, node number of first male and female flowers, total number of fruits and number of melon fruit-fly [Bactrocera cucurbitae (Coquillett),Diptera: Tephritidae] infected fruits were recorded. Snap melon being a monoecious and warmth loving crop, tends to bear increasing number of female flowers with time; days to first female flower gradually lessened from the first to the third sowing, which signify longer fruiting period from the first to the third sowing. The infestation level of fruit fly has been found to be higher in March sowing than the other two sowing dates, irrespective of the genotypes, and BCSM-4 was affected the least when sown in January or March by fruit fly. Considering earliness, total number of fruits per plant and moderately lower fruit fly incidence, BCSM-4 and BCSM- 8 may possibly perform better than the other genotypes in the lower Gangetic plain if sown during end of January.